Case Study : Flex Fisioterapi / Ahmad Nur’alif Mohamad Nadzir - Mohamad Nadzir, Ahmad Nur’alif (2020)
Flex Physiotherapy prepare physiotherapy treatments to those who suffer from back pain, sport injuries, stroke, special children, neck pain, shoulder and knee problem for all ages. This treatment centre is complete with the treatment by experience physiotherapists and spinal adjustment specialist